Online Communities, Brand Recovery, Consumer Relationships, and Repurchase Intention - Mohammad Allatas Muryanto; Ifta Firdausa Nuzula; Thangaraj Venkatesan (The Indonesian Institute of Science and Technology Research, 2023)
This study examines the influence and linkages between Online Communities, Brand Recovery, Consumer Relationships, and Repurchase Intentions. The case discussed is Tokopedia as one of the big market places in Indonesia. The research uses a quantitative approach with instruments in the form of questionnaires distributed to Tokopedia users. Questionnaire distributed online. The respondent's response is a scale from 1(strongly disagree) to 5 (strongly agree). The data is processed using the Structural Equation Modeling (SEM) model. Brand recovery efforts have a significant positive effect on consumer forgiveness. If users experience high brand recovery efforts, they will also have high consumer forgiveness. Brand restoration efforts have a significant positive impact on repurchase intentions. Online brand community involvement has a significant positive effect on consumer forgiveness. Users were involved in an increased online brand community and will also have high consumer forgiveness. Online brand community involvement has a positive but insignificant effect on repurchase intention.